Exploring psychology in modules - Myers, David G. (Worth Publishers, 2008)
Exploring Psychology, Seventh Edition, in Modules is the modular version of the bestselling brief introduction to psychology: David Myers' Exploring Psychology. All the Myers hallmarks are there--the captivating writing, coverage based on the latest research, helpful pedagogical support--in a format that delivers the utmost in student accessibility and teaching flexibility.